The Relationship Between Dermatologist- and Patient-Reported Acne Severity Measures and Treatment Recommendations. Issue 5 (September 2015) - Tan, Jerry; Frey, Marc P.; Knezevic, Sanja; Poulin, Yves; Lynde, Charles W.; Gulliver, Wayne P.; Gupta, Aditya K.; Sebaldt, Rolf J.; Thomas, David R.; Sapra, Sheetal
Background: Acne treatment recommendations for individual patients may be derived from multiple factors including dermatologist- and patient-reported constructs. Objectives: To evaluate the effects of dermatologist- and patient-reported measures on acne treatment recommendations by dermatologists. Methods: An observational cross-sectional survey of acne patients was conducted with patient-reported quality of life and dermatologist-reported measures of primary and secondary (scar) acne severity using 3 assessment approaches: maximal regional grade, total grade, and facial grade. Results: The most highly associated factors with acne treatment recommendations were patient emotions, maximal regional acne severity, and total acne scar grade. Better acne-specific quality of life was negatively related to acne treatment recommendation intensity, while all 3 grading approaches were positively related to acne treatment recommendations. Conclusions: For dermatologists, overall acne severity is most highly associated with maximal regional acne grade, total scar grade, and patient's emotional response to acne.